FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BEI - Nadya Tamara Halim; Viriany Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this research is to analyze whether profitability and leverage affect company value, and to see the ability of company size to moderate this relationship in food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sample for this study was selected through a non-probability sampling technique, precisely purposive sampling, and the valid data were 23 companies. Data analysis using descriptive statistics, classical assumption tests, panel data regression hypothesis testing and moderated regression analysis (MRA) assisted by the Eviews program version 12 and Microsoft Excel 2013. The results of this study indicate that profitability and leverage have no significant effect on firm value. Firm size can moderate the effect of profitability on firm value but cannot moderate the effect of leverage on firm value. The implication of this research is that companies need to improve their capabilities so that they can be more effective in managing the company so that it will increase the value of the company which will provide a good signal and attract investors.